Method for increasing the efficiency of guidance of an unmanned aerial vehicle at high speed and higly maneuverable targets - A. V. Lopuhov; A. A. Babchenok (Системный анализ и прикладная информатика, 2020)
The purpose of the article is to increase the efficiency of the use of an unmanned aerial vehicle (UAV), when pointing it at high-speed and highly maneuverable targets, through the use of a combined method of creating control forces and moments, as well as the synthesis of an onboard stabilization system (UAV), based on a multidimensional nonlinear dynamic model.The combined control algorithm is based on a combination of aerodynamic and gas-dynamic methods of creating forces and moments. In this case, switching modes from aerodynamic to gas-dynamic control are taken into account, including the features of the synthesis of the stabilization system on the bases of the synergetic control theory and the processes of its dynamics.Simulated mathematical modeling of UAVs with a combined control method and a synthesized controller was carried out. The synthesis of the onboard stabilization system controller is based on the introduction of attractor states into the space, which ensure the formation of the necessary UAV properties. The synthesized controller implements the required technological tasks and the stability of the aircraft.The need to use the aerodynamic control method and synthesis of the stabilization system regulator is due to the growth of the tactical and technical characteristics of aerospace attack facilities, which will ensure high efficiency of UAV application for high-speed and highly maneuverable targets.